2016
DOI: 10.1007/978-94-6300-432-9
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Materials Development

Abstract: As a praxis-based sequence these texts are specifically designed by the team of international scholars to engage in local in-country language pedagogy research. This exciting and innovative series will bring a dynamic contribution to the development of critical new literacies. With a focus on literacy teaching, research methods and critical pedagogy, the founding principle of the series is to investigate the practice of new literacies in English language learning and teaching, as negotiated with relevance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Carabantes and Paran (2017) stated that materials development and use are still the central core of language teaching, and ELT teachers should be trained to use digital materials for effective teaching and learning. Materials development is a core component that must be emphasized in all teacher training programmes (Tomlinson, 2016), and he confirmed that most ELT classrooms around the world are based on materials. Thus, training of teachers to develop and use both print and digital media is important.…”
Section: Statement Of Problemmentioning
confidence: 86%
See 2 more Smart Citations
“…Carabantes and Paran (2017) stated that materials development and use are still the central core of language teaching, and ELT teachers should be trained to use digital materials for effective teaching and learning. Materials development is a core component that must be emphasized in all teacher training programmes (Tomlinson, 2016), and he confirmed that most ELT classrooms around the world are based on materials. Thus, training of teachers to develop and use both print and digital media is important.…”
Section: Statement Of Problemmentioning
confidence: 86%
“…The application of modern technology represents a significant advance in contemporary English language teaching methods (Alqahtani, 2019). However, it must be noted that teachers must be trained to develop materials that are content and context appropriate (Tomlinson, 2016) using both print and digital technology resources. Tomlinson (2016) also asserted the need for materials development training component in all ELT teacher training programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation